Man And Redemption - Łydka, Władysław (Studia Theologica Varsaviensia, 2020)
What conclusions of the Pope’s doctrine are significant for our way of teaching the treaty on Redemption? /) e lecture should include an analysis of the concrete existential situation of today’s individual, our nation and all modern humanity. Awareness of the contemporary existential situation and contemporary conditions should be both a starting point in the considerations on the Redemption, their relevance and indispensability, as does political theology or liberation theology in their own way, and the basis which makes it possible that lectures on Redemption would demonstrate its significance for today’s man and teach people effective concern for specific matters of existence of Others. When talking about the effects of Redemption, one should ask what is its significance today for human existence, for example in the burning matter of human dignity and rights, or in the field of the Church’s tasks in the world. us, both the starting point and effects of the Redemption should be presented in a concrete way, in relation to the current socio-historical situation, based on current experience. () All teaching on the Redemption should be based on biblical sources, obviously interpreted in light of the last Council and entire Christian Tradition. Referring – to a greater extent – to the content and statements presented in the Bible, may help to overcome the abstractness and the one-sidedness of traditional soteriological treaties, which consider Redemption only in terms of substitute compensation, the most perfect sacrifice and individualistic and ethical participation in the atonement and merits of Christ. X) It is necessary to harmoniously combine – as the Pope does in his Encyclical – various aspects of the doctrine of the Redemption, o6en interpreted separately in earlier theological treaties. In the spirit of such a harmonious synthesis, it is necessary to demonstrate the relationship between the work of Redemption and the work of creation, between the Incarnation and the Passover of Christ, between man’s Redemption and the Redemption of the whole world, between moral liberation from sin and social liberation from all forms of oppression, the concern for eternal salvation and for authentic humanism in earthy life. Z) Among many biblical categories that provide a closer view on the mystery of Redemption, it is especially important to present the category of love, not only in order to overcome the narrow, legal and social approach to Redemption in terms of satisfaction and merit, but above all because love is a preeminent category in the theory of Christian revelation, the attitude and action most appropriate for God and for every human being, and the source or bond of true and full communion between people and God. 9) One should teach about the Redemption using a concrete language, and not the abstract one. When analyzing the biblical texts it is necessary to explain that the revelation of the mystery of the Redemption took place gradually, within the framework of history, in the context of certain cultural categories, that people were redeemed from the situation of sin through concrete events, carried out by God throughout history, especially through life, death and resurrection of Christ. e Christ who lived in a certain place and in a certain time carried out the Redemption by restoring the broken covenant of mankind with God, and today He allows us to enjoy the effects of the Redemption. rough meeting and uniting with Him in faith and love, confirmed and strengthened in the sacraments, each person regains the highest dignity and the possibility of full development. us, the teaching on Redemption using a concrete language will be thus also tantamount to emphasizing the historical, Christocentric and personalist character of Redemption. Y) Finally, following the biblical approach, one should refrain from confining oneself to recognize the mystery of the Redemption in a purely objective and essentializing manner – which was common in earlier textbooks – from carrying out considerations about its essence in isolation from man and his situation, but instead one should try to recognize this mystery in terms of its role in human life and humanity, its significance for specific human history, its influence on human activity and human culture.